Implementation of Sensor Ph Meter, Ec Meter and Temperature on Smart Vertical Agriculture System - A Cucus; M S Febrianti (International Conference on Engineering and Technology Development (ICETD), 2017)
In this study the area discussed is how to apply the sensor on the Smart Vertical Agricultural System. This system applies information technology on urban agriculture technique that utilizes water as planting medium. Application of technology is used to help human beings in controlling, maintaining the stability of the water content needed by plants in order to develop properly. Development of the Smart Vertical Agriculture System, will focus on hardware as a water stabilizer, as well as websites connected with the device, so that hydroponic owners will be able to monitor plant progress through the website. In this research we will build prototype of robotics device using arduino, raspberry pi 2, some sensors such as temperature sensor, nutrition sensor and Ph sensor, effector in the form of pump, water cooling device, and electric valve, data collection of plant knowledge for machine learning needs to make decisions, as well as centralized database mining to manage multiple devices